Development of A Decision Support System on Employee Performance Appraisal using AHP Model - Stephen Gbenga Fashoto; Onyebuchi Amaonwu; Adenrenle Afolorunsho (JOIV : International Journal on Informatics Visualization, 2018)
Many employees’ performance appraisal systems lack business standard irrespective of the organization. Performance appraisal system differs depending on the type of work and job description in an organization. Most organizations lack scientific technique for rating their employee’s performances. In this case, a decision support system will help organizations to have a standardize way of performance appraisal and make the appraisal process transparent, fair and just. Analytical Hierarchy Process (AHP) was used in this paper to evaluate employees performances based on five criteria: personal skills, initiatives, teaching quality, method of teaching and research in which case each of the criteria was divided into sub-criteria; and by applying the Decision Support software for evaluating employees performance in line with the individual objectives required to meet the overall organizational mission. The result obtained showed that the consistency ratio (CR) of the five criteria is C.R = 0.0976 which showed that there is consistency in all the criteria in appraising the performance of an academic staff in Kampala International University (KIU) except research. Therefore, personal skills, initiatives, teaching quality and method of teaching are consistent and valid factors while research has not been consistent in appraising an academic staff in KIU despite the weight (47%) attached to it.